International history of the twentieth century and beyond - Best, Antony. 1964-; Hanhimaki, Jussi M. 1965-; Maiolo, Joseph A.; Schulze, Kirsten E. (London ; New York : Routledge, Taylor & Francis Group, 2025)
"Now in its fourth edition, this highly successful global history of the twentieth century is written by four prominent international historians for first-year undergraduate level and upward. The book is supported by a fully revised companion website including links to further resources and self-testing material, which can be found at www.routledgelearning.com/internationalhistory20c"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: World politics -- 20th century; World politics -- 21st century